(untitled) (Research, Society and Development, 2020)
The improper disposal of residual whey from dairy production represents a serious environmental problem in Brazil, causing a lot of effort applied in the development of dairy products with partial replacement of milk by whey. In this study, three formulations of a frozen dairy drink containing whey and different amounts of fructooligosaccharides, in replacing saccharose, were developed and evaluated in relation to physicochemical, microbiological and sensory properties. All physicochemical and microbiological parameters were within Brazilian regulations for frozen edibles. Evaluated by 120 volunteers, the Acceptability Index was above 80% for all formulations and attributes and the purchase intention favourable the acquisition of the product. The tested formulations represent a nutritious and safe alternative for the use of residual whey from dairy farms and an innovation on the market of functional frozen edibles.